2011
DOI: 10.1128/jvi.00757-11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Retromer Activity by Herpesvirus Saimiri Tip Leads to CD4 Downregulation and Efficient T Cell Transformation

Abstract: The mammalian retromer is an evolutionally conserved protein complex composed of a vacuolar protein sorting trimer (Vps 26/29/35) that participates in cargo recognition and a sorting nexin (SNX) dimer that binds to endosomal membranes. The retromer plays an important role in efficient retrograde transport for endosome-to-Golgi retrieval of the cation-independent mannose-6-phosphate receptor (CI-MPR), a receptor for lysosomal hydrolases, and other endosomal proteins. This ultimately contributes to the control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 54 publications
4
39
1
Order By: Relevance
“…CSC deficiency plays a role in nonamyloidogenic versus amyloidogenic processing of amyloid precursor protein (APP) (He et al 2005;Small et al 2005;Muhammad et al 2008;Wen et al 2011;Choy et al 2012) and the pathogenesis of Alzheimer's disease (Siegenthaler and Rajendran 2012). In addition, a specific VPS35 mutation, Asp620Asn, has been linked to late-onset autosomal-dominant familial Parkinson's disease (Vilariño-Güell et al 2011;Zimprich et al 2011), the loci for human VPS26A has been genetically associated with type 2 diabetes in South Asians (Kooner et al 2011), and the endosomal transport of various pathogens (Salmonella, Herpesvirus saimiri, Coxiella burnetii, human papillomavirus, Legionella pneumophila) and toxins (Shiga toxin) is also mediated in part by the CSC Popoff et al 2007;Kingston et al 2011;Finsel et al 2013;Lipovsky et al 2013;McDonough et al 2013). …”
Section: The Diversity Of Retromer Function In Cell Function and Orgamentioning
confidence: 99%
“…CSC deficiency plays a role in nonamyloidogenic versus amyloidogenic processing of amyloid precursor protein (APP) (He et al 2005;Small et al 2005;Muhammad et al 2008;Wen et al 2011;Choy et al 2012) and the pathogenesis of Alzheimer's disease (Siegenthaler and Rajendran 2012). In addition, a specific VPS35 mutation, Asp620Asn, has been linked to late-onset autosomal-dominant familial Parkinson's disease (Vilariño-Güell et al 2011;Zimprich et al 2011), the loci for human VPS26A has been genetically associated with type 2 diabetes in South Asians (Kooner et al 2011), and the endosomal transport of various pathogens (Salmonella, Herpesvirus saimiri, Coxiella burnetii, human papillomavirus, Legionella pneumophila) and toxins (Shiga toxin) is also mediated in part by the CSC Popoff et al 2007;Kingston et al 2011;Finsel et al 2013;Lipovsky et al 2013;McDonough et al 2013). …”
Section: The Diversity Of Retromer Function In Cell Function and Orgamentioning
confidence: 99%
“…The 293T cells were transfected with genes encoding myc-tagged VPS26, VPS29, and VPS35, or an empty vector (44). Thirty hours later, cells were infected with HPV16.L2HA-GFP at an MOI of 50 for 8 h and then lysed in buffer containing 1% Nonidet P-40.…”
Section: Methodsmentioning
confidence: 99%
“…Snx3 has been implicated in the maturation of Salmonella-containing endosomes, although it is not yet clear whether in this role Snx3 is associated with retromer proteins (Braun et al, 2010). Additionally, the Tip protein of Herpes virus can bind to Vps35 to inhibit retromer function, leading to reduced CIMPR levels and downregulation of CD4 (Kingston et al, 2011), and entry of Vaccinia virus has been shown to require the Fam21 subunit of the WASH complex (Huang et al, 2008).…”
Section: Retromer and Diseasementioning
confidence: 99%